Fabrication of Electrospun Nanofibers Membrane for Emulsified Oil Removal from Oily Wastewater (Baghdad Science Journal, 2022)
The electrospun nanofibers membranes have gained considerable interest in water filtration applications. In this work, the fabrication and characterization of the electrospun polyacrylonitrile-based nonwoven nanofibers membrane are reported. Then, the membrane's performance and antifouling properties were evaluated in removing emulsified oil using a cross flow filtration system. The membranes were fabricated with different polyacrylonitrile (PAN) concentrations (8, 11, and 14 wt. %) in N, N-Dimethylformamide (DMF) solvent resulted in various average fiber sizes, porosity, contact angle, permeability, oil rejection, and antifouling properties. Analyses of surface morphology of the fabricated membranes before and after oil removal revealed increasing the fiber size, decreasing the fouling amount, and increasing the permeate flux. On the other hand, decreasing the fiber size resulting in increases the oil rejection. It was observed that 11 wt. % PAN based nonwoven nanofiber membrane was the optimum membrane for emulsified oil removal due to its good porosity, permeability with good oil rejection. In addition, fouled nonwoven nanofiber membrane cleaning was done by backwashing technique using warm distilled water which was effective in retaining the membrane permeability and oil rejection for 7 times. The obtained results confirmed an efficient performance of the fabricated nanofibers membrane for oil-water separation with oil rejection percentage of 92.5% and a permeate flux of 120 LMH.